Research Perspectives in Couple Therapy Discursive Qualitative Methods - Borcsa, Maria; Rober, Peter (Springer International Publishing : Imprint: Springer, 2016)
In this powerful volume, six qualitative methods are used to analyze a couple therapy with a troubled young couple, illustrating the intricate processes and sub-processes of therapy through client interactions with their therapists and with each other. Increasingly popular for revealing the nuances and complexity of human interactions, qualitative approaches focus on process and discursive methods which can be particularly rewarding in multi-client settings. Through the examples that make up the text, practitioners and researchers become better acquainted with the power of qualitative perspectives and are encouraged to examine their own views on therapy as they consider these and other concepts: The development of dialogical space in a couple therapy session. Introducing novelties into therapeutic dialogue: the importance of minor shifts of the therapist. Therapists' responses for enhancing change through dialogue: dialogical investigations of change. Fostering dialogue: exploring the therapists' discursive contributions in a couple therapy. Dominant story, power, and positioning. Constructing the moral order of a relationship in couples therapy. Research Perspectives in Couple Therapy: Discursive Qualitative Methods ably demonstrates the balance between therapeutic art and science for family and couples therapists, psychologists, and other mental health professionals in research and practice.